The Concept of Arisan Syariah and Accounting Recording for the Libersa Tambun Housing Mothers - Neng Asiah; Listian Indriyani Achmad; Adibah Yahya; Sheila Wahyuni (Pasundan Community Service Development, 2023)
The Community Service activity is motivated by the activities of the women in Libersa Tambun housing complex regarding investment management. One of the regular activities they engage in is arisan, a financial system that lacks legal regulations and solely follows traditional practices in the community. The mothers in Libersa housing complex have been conducting arisan activities without understanding whether the arisan transactions they have been participating in comply with Islamic principles or not. From an accounting perspective, arisan can be seen as a form of debt, but in Islamic principles, arisan can be conducted as long as it does not involve usury (riba). Mentoring on the concepts of accounting in arisan and Islamic principles becomes the method employed in the Community Service activity, with the aim of helping the mothers understand the differences between investment and arisan from the perspective of Islamic accounting. The results of the activity indicate that the participants comprehend the concept of arisan based on Islamic principles and are able to perform accounting records for transactions within arisan.